Evaluating the Effectiveness of a Multimedia Program on Home Safety. - Sweeney, Mary Anne; Chiriboga, David A. (Gerontologist, 2003)
Purpose: This study was designed to test the effectiveness and acceptance of multimedia home safety programming by community-dwelling seniors. Design and Methods: A prototype CD-ROM was produced that required no reading or computer skills because the program included an audio narration of content and directions for operating the program on a touchscreen computer monitor. Volunteers (N = 126) from a senior center aged 55 and older were randomly assigned to (1) a multimedia group that used the interactive program to learn about home safety, (2) a traditional learning group that read well-established booklets on home safety, and (3) a control group that received no instruction on safety between the pre- and posttests. Results: Repeated-measures multivariate analysis of variance showed that the multimedia group was the only group to improve in knowledge. The group was also very satisfied with the approach. Implications: Multimedia formats can effectively and economically provide information to older clients. Reprinted by permission of the publisher.